Scorpion maintenance in captivity for venom extraction in Costa Rica - Brenes, Emanuel (2016)
Approximately 2 000 scorpion species can be found around the world; although few species are considered “harmful” to human beings, a high number of scorpionism cases are reported all over the world. The elaboration of anti-scorpion sera requires the establishment of an animal collection maintained in captivity for venom extraction purposes. The Clodomiro Picado Institute (ICP, for its acronym in Spanish), poses a vast tra-jectory in manufacturing snakebite antivenoms, and starts a scorpion collection in 2005 for this purpose. In total, 2 043 scorpions were classified in 11 species and collected during a seven-year period using a black-light flash-light and an intensive seeking methodology. The scorpions were collected from several localities of the Pacific and the Caribbean versants of Costa Rica. The venom extraction was performed by applying electrostimulation; the collected venom was characterized by total protein content in addition to median lethal doses. Centruroidesbicolor showed higher amounts of venom yield, total protein content and more lethal dose, all of which were cor-related with its body mass. The techniques used to keep scorpions in captivity allowed the animals to live several years. Longevity analysis showed significant differences among scorpion genera (H= 353.80; df= 3; P < 0.0001); moreover, the genus Didymocentrus lived longer with an average of 4.46 years. One key factor of its longevity was that it did not go through venom extraction processes. Additionally, a high survival rate of Tityuspachyurusborn in captivity, compared to other species within the same genus, was observed (H= 94.32; df= 3; P < 0.0001). This characteristic should be taken into consideration, when programs of reproduction in captivity are designed. In conclusion, the maintenance of a scorpion collection was efficient for venom extraction purposes and a longer life expectancy of the animals. Moreover, there is a scarcity on publications regarding scorpion maintenance in captivity for venom extraction purposes; therefore, a deeper research in aspects such as reproduction, death causes and feeding behaviors is required. Rev. Biol. Trop. 64 (3): 1019-1027. Epub 2016 September 01.